An Examination of the International Federation of Agricultural Journalists' Involvement in Agriculture Knowledge Mobilization - William Nelson; David L. Doerfert; Courtney Meyers; Matt Baker; Cindy Akers; Masaru Yamada; Teruaki Nanseki; Owen Roberts (Journal of Applied Communications, 2014)
It is estimated the global population will reach 9 billion by the year 2050. This growth in population presents a very imposing problem for agriculture. A potential solution to increasing agricultural production is the mobilization of information through agricultural innovation systems. What has not been studied is the role the International Federation of Agricultural Journalists (IFAJ) has in this system. This study sought to describe the IFAJ and its membership’s knowledge mobilization role within Agricultural Knowledge and Innovation System (AKIS), describe the issues facing the membership related to agricultural innovation systems, and record the practices members feel are best to identify stories of interest, create media pieces, and disseminate those media pieces. The results of the study indicate the majority of respondents work as journalists/reporters and a large portion of organizations employ fewer than five people. In respect to the AKIS model, the largest portion of respondents saw themselves as facilitators of knowledge movement. Despite some similarities, differences were revealed between the employment category types found within the IFAJ membership in their perceived objectivity when it comes to their role within AKIS. Talking to stakeholders was the most popular method of identifying stories of interest, involving the farm perspective was most popular strategy for the creation of interesting media pieces, and the use of digital and traditional media was the most popular method to disseminate their work. As IFAJ continues its dedication to providing helpful information to the world ’s farmers, the organization should realize its membership is not unified in its approach.
Keywords: Agricultural knowledge mobilization; best practices; source trust; knowledge; knowledge transfer